2004
DOI: 10.1590/s0102-05362004000300015
|View full text |Cite
|
Sign up to set email alerts
|

Tratamentos de erradicação de Xanthomonas vesicatoria e efeitos sobre a qualidade das sementes de tomate

Abstract: Comparou-se a eficiência de tratamentos físicos e químicos na erradicação de X. vesicatoria em sementes de tomate 'Santa Clara Miss Brasil' e avaliou-se os seus efeitos sobre as qualidades fisiológica e sanitária das mesmas. As sementes foram inoculadas a vácuo com o isolado ENA 4463 de X. vesicatoria, e secas em estufa com ventilação à temperatura de 35ºC, até atingirem 8% a 9% de teor de água. Compararam-se os tratamentos, HCl a 5%, por 10 minutos, calor seco (70ºC/96 horas) e imersão em água a 50ºC, durante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 8 publications
0
7
0
8
Order By: Relevance
“…In seeds, the elimination or reduction of the infective inoculant of fungi has been efficiently achieved through chemical, biological and physical treatments (ESTEFANI; MIRANDA FILHO; UESUGI, 2007). Among the physical methods, the effectiveness of thermotherapy, which consists of exposing the seeds to the action of heat combined with the time of treatment, has been demonstrated in some studies (CARMO et al, 2004;LOPES;ROSSETTO, 2004;OLIVEIRA et al, 2011). However, for this method to be successful, it is necessary to know the correct combination of temperature and exposure time, which may vary with the species, cultivar, batch, initial vigour and other factors.…”
Section: Introductionmentioning
confidence: 99%
“…In seeds, the elimination or reduction of the infective inoculant of fungi has been efficiently achieved through chemical, biological and physical treatments (ESTEFANI; MIRANDA FILHO; UESUGI, 2007). Among the physical methods, the effectiveness of thermotherapy, which consists of exposing the seeds to the action of heat combined with the time of treatment, has been demonstrated in some studies (CARMO et al, 2004;LOPES;ROSSETTO, 2004;OLIVEIRA et al, 2011). However, for this method to be successful, it is necessary to know the correct combination of temperature and exposure time, which may vary with the species, cultivar, batch, initial vigour and other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al (2013) reported transmission and infection by Xanthomonas vesicatoria from seed integument to new shoots of tomato seedlings (Solanum lycopersicum L.). Although seed transmission rate is low (Saettler et al, 1989;Carmo et al, 2004), seeds can act as efficient vectors for spreading bacteria (Romeiro, 2005) if the initial inoculum is introduced into growing areas (Carmo et al, 1996;Carmo et al, 2004;Romeiro, 2005;Silva et al, 2013). For example, the transport of bacteria from complex X. vesicatoria by tomato seeds (S. lycopersicum) is a major mechanism of survival and spread of the pathogen (Carmo et al, 2004;Jones et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although seed transmission rate is low (Saettler et al, 1989;Carmo et al, 2004), seeds can act as efficient vectors for spreading bacteria (Romeiro, 2005) if the initial inoculum is introduced into growing areas (Carmo et al, 1996;Carmo et al, 2004;Romeiro, 2005;Silva et al, 2013). For example, the transport of bacteria from complex X. vesicatoria by tomato seeds (S. lycopersicum) is a major mechanism of survival and spread of the pathogen (Carmo et al, 2004;Jones et al, 2004). Thus, seed-borne bacteria can be efficiently disseminated over long distances and introduced in areas free of disease, or may serve as a source of initial inoculum for epidemics in nurseries and fields (Neergaard, 1979;Romeiro, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…(MUNIZ, 2001); Alternaria alternata (MUNIZ, 2001;TOGNI et al, 2005); Phoma sp. (NASCIMENTO;MORAES, 1990); Pseudomonas tomato (NASCIMENTO;MORAES, 1990); Xanthomonas vesicatoria (McMILLAN Jr., 1987;NASCIMENTO;MORAES, 1990;SILVA et al 2002;CARMO et al, 2004); Clavibacter michiganense subsp michiganense (Smith) (SHOEMAKER;ECHANDI, 1976;IKUTA, 1990;NASCIMENTO;MORAES, 1990) e TMV (REES, 1970), como agentes causadores de doenças do tomateiro, de acordo com Kurosawa e Pavan (1997). Somando-se a esses, a Didymella lycopersici (KASSELAKI et al, 2008) pode estar associada às sementes, mas não é agente causador de doenças no tomateiro.…”
Section: Revisão Bibliográficaunclassified
“…(NASCIMENTO;MORAES, 1990;DINIZ et al, 2006); Cladosporium fulvum (MUNIZ, 2001) e Erwinia spp. (SILVA et al 2002;CARMO et al, 2004;. Por outro lado, muitos, também citados na literatura, não são agentes causadores de doenças para o tomateiro, mas podem reduzir o vigor das sementes, como:…”
Section: Revisão Bibliográficaunclassified